Los esgrafiados sobre cerámica de Ca n’Oliver (Cerdanyola del Vallès) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to offer an integral edition of Greek and Iberian inscriptions found in the site of Ca n'Oliver (Cerdanyola del Vallès).
Keywords: Ca n’Oliver; Epigraphy; Iberian Language; Greek Anthroponomy; Iberian Anthroponomy